Analisis Pengaruh Kualitas Pelayanan Customer Service Terhadap Kepuasan Nasabah - Meldi Manuhutu; Zany Irayati Aunalal; Maudy Tanihatu (Universitas Muhammadiyah Jember, 2021)
This study aimed to determine the effect of tangibles, reliability, responsiveness, assurance, and empathy from customer service performance to customer satisfaction at PT. Bank Tabungan Negara (Persero), Tbk Ambon Branch Office both simultaneou and partialy. The sample used in this study was 150 samples. The research method used descriptive and quantitative methods with multiple linear regression data analysis techniques. The results of this study indicate that simultaneous tangibles, reliability, responsiveness, assurance, empathy variables have a significant and positive effect on customer satisfaction and only partially responsiveness variable which have no significant effect on customer satisfaction. The influence of service quality variables on customer satisfaction at PT. Bank Tabungan Negara (Persero), Tbk Ambon Branch is 70 % that influence is very strong while the other 30% is influenced by the other variables.